The Use of Visual Aids to Enhance EFL Students’ Literature Understanding The Case Study of Second-year Studentsat The Department of English-Universityof Laghouat - Kherici,Chaima; Aribi, Ibrahim (Faculty of Letters and Foreign Languages Department of English, 2024)
Visualaids have become increasingly popularin various educational fields, including literature. Dissertation outlinesthe increasingpopularity of visual aids in educational fields, particularly in literature,to enhance teaching methodsand student engagement.The study evaluates visual-based instruction throughmethods such as role-playing, movie adaptations, and posters as educational tools forteachingEFLliterature to second-year students atthe University of AmarThelidji. The specific objectives include exploring the effectsof visual aids onliterary understandingand expanding students' experienceswith literature.The researchutilized two instruments: aquestionnaire forsecond-yearstudents inwhich 30students were asked inorderto conclude withfindingand a semi-structured interviewwithfive literary teachers. Findings indicated that students benefited from visual aids,becomingmore engaged in the learning process. The study concluded thatvisualaids facilitate literature studies and allowteachersto integrate online contentwith face-to-face instruction. Itsuggeststhatthe use ofvisual aids in literature classes providesa foundation for further investigation into theirintegration intraditionaleducationalsettingsto supporteffective teachingand learning proccesses